The Relevance of Islamic Law to Criminal Sanctions for Narcotics Users in Indonesia - Muhibban, Muhibban; Misbakul Munir, Muhammad (Riviera Publishing, 2023)
The increasing number of drug users netted in Indonesia has made prisons and detention centres over capacity. The high number of narcotics cases has filled prisons and detention centres, mainly with those who stumble on narcotics cases. This study aims to describe Islamic punishments for cases of drug users that are relevant, based on benefit and does not cause new polemics. This type of research is library research using a descriptive-analytic method by looking for primary and secondary references related to this study. Based on the results of the analysis, it is stated that sanctions against drug users have so far not yielded good results and have even created several new polemics. Meanwhile, Islamic punishment, ta'zir, is more appropriate and relevant to narcotics users. Ta'zir punishment is preventive, which can prevent a person from getting away from drugs; repressive, which makes offenders deterrent; curative, which can provide changes in the perpetrators; and educative, both for drug offenders and other people. The implementation of Law No. 35 of 2009 on narcotics is still unable to overcome the problem of drug abuse properly, even causing new problems such as exceeded prison capacity, increased state budget burden, and punishments that do not have a positive impact on perpetrators. Islamic punishment, with a more humane and effective approach, can be a viable alternative to address this problem.